2013
DOI: 10.1111/aor.12159
|View full text |Cite
|
Sign up to set email alerts
|

Early Classic Hemofiltration Exhibits No Benefits in Severe Acute Pancreatitis With Early Organ Failure: A Retrospective Case-Matched Study

Abstract: Continuous venovenous hemofiltration (CVVH) is an important organ supportive technique. This study aimed to evaluate the impact of early classic CVVH on the outcomes of severe acute pancreatitis (SAP) patients with early organ failure (EOF). Between 2008 and 2012, a total of 44 SAP patients with EOF were admitted to our department. The 44 patients were classified into two groups according to whether they received early classic CVVH (2 L/h, initiated within 24 h after admission): 25 patients received early CVVH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
1
11
1
Order By: Relevance
“…For example, patients received continuous hemofiltration treatment according to whether there exists a complication but not the grouping plan [9]. (6) SAP patients in the control group received continuous hemofiltration therapy after the onset of treatment [7,10]. (7) Apart from the continuous hemofiltration therapy, patients in the study group receive traditional Chinese medicine, plasma exchange, hemoperfusion, or other kinds of combination therapies [11,12].…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, patients received continuous hemofiltration treatment according to whether there exists a complication but not the grouping plan [9]. (6) SAP patients in the control group received continuous hemofiltration therapy after the onset of treatment [7,10]. (7) Apart from the continuous hemofiltration therapy, patients in the study group receive traditional Chinese medicine, plasma exchange, hemoperfusion, or other kinds of combination therapies [11,12].…”
Section: Study Selectionmentioning
confidence: 99%
“…As cytokines and inflammatory products excessively released during the pathological process of SIRS in SAP are considered to be crucial mediators leading to MODS, continuous hemofiltration could remove these inflammatory mediators from the circulation by means of convective filtration, dispersion, and adsorption, blocking the pathological process and eliminating the cytokine cascade [ 4 – 6 ]. Despite some study opposing the benefits brought by the continuous hemofiltration for SAP, most studies have reported the effectiveness of continuous hemofiltration on SAP and its complications, but there are still some items such as abdominal pain relief, the cost of hospitalization, and the need for surgery that need to be further explored [ 7 , 8 ]. The superiority of continuous hemofiltration for SAP needs to be well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, according to many authors, CVVH application was useful in patients with critical state including those with AP since it improved the course of the disease, eliminated toxic substrates, stabilized hemodynamics, reduced lethality [34,38,44,46,75,77,91,109,[113][114][115][116][117][118][119]. But at the same time, some investigators did not demonstrate convincing advantages of CVVH in patients with sepsis, septic shock, SAP, and MOFS [53,67,73,[120][121][122].…”
Section: Hemofiltration and Hemodiafiltration In Severe Acute Pancreamentioning
confidence: 99%
“…prior to a full-scale clinical and laboratory picture of MOFS in order to prevent its development and progression. Until now there have been different opinions on the criteria of early beginning of continuous RRT in patients with MOFS of different etiology [ 4 , 34 , 38 , 55 , 71 , 73 , 77 , 81 , 91 , 105 , 109 , 113 , 116 , 117 , 121 , 133 ]. On the one hand, application of continuous RRT before MOFS involves high economic expenditures related to the procedure.…”
Section: Hemofiltration and Hemodiafiltration In Severe Acute Pancreatitismentioning
confidence: 99%
“…Xujie Zhang et al. of the Fourth Military Medical University, Xi'an, China, reported on a retrospective case‐matched study of patients with severe acute pancreatitis (SAP) with early organ failure (EOF); 19 patients each either received continuous venovenous hemofiltration (CVVH) or not (control). The study failed to prove that early classic CVVH had any benefits on the outcomes of SAP patients with EOF.…”
Section: Renal Support and Dialysismentioning
confidence: 99%